(untitled) (Innovative professional education, 2025)
For the most part, in the practice of professional training of a competent specialist, attention is focused on the selection of the necessary educational material, the interaction of the teacher (master of industrial training) and the student, while the need for cooperation of the students themselves is often overlooked. The study determines that the level of learning of educational material, how students will feel, how their independence, self-awareness, and professional competencies will be formed depends on the interaction in the classroom effectively organized by the teacher.